2021
DOI: 10.3390/nu13082500
|View full text |Cite
|
Sign up to set email alerts
|

Social Inequalities in Breakfast Consumption among Adolescents in Spain: The DESKcohort Project

Abstract: Breakfast has a critical role in energy balance and dietary regulation. Consequently, it is considered an important component of a healthy diet, especially in adolescence, when there are great opportunities to consolidate habits and establish future patterns of healthiness in adulthood. Socioeconomic position (SEP) causes inequalities that are reflected in health behaviors, physical activity, mental health, and diet. Therefore, we conducted a cross-sectional study using data from the 2019–2020 DESKcohort proje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 74 publications
(98 reference statements)
0
15
1
Order By: Relevance
“…In our study, 28.8% and 24.7% of the respondents skipped breakfast on weekdays and at weekends, respectively, a behavioral trait that has been identified as typical among young people 3 , 12 , 13 , 54 , including vocational school students in Finland 28 . Also, lower socioeconomic position is one significant risk factor for skipping breakfast 55 . Previous research has also found that girls frequently skip breakfast and eat less often with family 1 , 3 , 4 , 11 , 14 .…”
Section: Discussionmentioning
confidence: 99%
“…In our study, 28.8% and 24.7% of the respondents skipped breakfast on weekdays and at weekends, respectively, a behavioral trait that has been identified as typical among young people 3 , 12 , 13 , 54 , including vocational school students in Finland 28 . Also, lower socioeconomic position is one significant risk factor for skipping breakfast 55 . Previous research has also found that girls frequently skip breakfast and eat less often with family 1 , 3 , 4 , 11 , 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Other cited reasons for missing breakfast include a lack of time, no enjoyment of breakfast or not feeling hungry in the morning, and weight control, especially in adolescent girls (de la Hunty et al., 2013; Sincovich et al., 2022). In the Spanish DESKcohort study including 7319 adolescents, breakfast skipping was suggested to be around 30% higher in adolescents in the most deprived compared to the least deprived groups (Esquius et al., 2021), and the authors suggested that this may be related in part to lack of access to, or availability of, food.…”
Section: How Common Is Breakfast Skipping In Young People?mentioning
confidence: 99%
“…In Korea, various indicators, including those related to nutrition, are set and monitored in the National Health Promotion Plan 2030. Taking into account the dietary behavior of adolescents along with these indicators, we considered 12 indicators of dietary behaviors; (1) family meal (yes), (2) nutrition education and counseling (yes), (3) use nutrition label (yes), (4) adequate fruit and vegetable intake (≥ 500 g/day of fruits and vegetables) [13,14], (5) calcium adequate intake (above the recommended intake of calcium, but below the upper limit), (6) Vitamin A adequate intake (above the recommended intake of Vitamin A, but below the upper limit), (7) skip breakfast (≥ 5 days/week), (8) excessive sodium intake (> 2,300 mg/day of sodium intake) [11], (9) excessive fat intake (> 30 persentages of total energy intake [E%]), (10) E p u b a h e a d o f p r i n t excessive sugar intake (≥ 10 E%), (11) frequent soft drink consumption (≥ 5 times/week), and (12) frequent eating out (≥ once/day).…”
Section: Variablesmentioning
confidence: 99%
“…A report from the Prospective Urban Rural Epidemiology study in 18 countries demonstrated that the availability, affordability, and consumption of fruits and vegetables depended on household income [ 4 ]. Furthermore, previous studies reported that dietary behaviors such as skipping breakfast and soft drink consumption were also related to household income [ 5 , 6 ]. The COVID-19 pandemic has caused socioeconomic changes such as an increase in the number of unemployed and a contraction in economic activity [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%